Design of a new clean and comfortable temperature-sensitive polyethylene-based copolymer textile - Wu, Zebin (Frontiers in Materials, 2023)
With the rapid development of science and technology, compared with traditional textiles, which provide basic functions such as shelter from the body and cold, intelligent textiles can create a more comfortable and safe environment for people, improve work efficiency and meet people's demand for diversified functions. At present, polypropylene material has the characteristics of temperature sensitivity, washing resistance, friction resistance, good whiteness and softness, and is widely used in textile, clothing and other industries. In this paper, The temperature sensitivity of cross-linked cotton fabric was characterized by measuring and analyzing the equilibrium swelling ratio, wetting time and surface contact angle. The temperature at which polymer properties suddenly change is 35℃, and the initial wetting time of cross-linked cotton fabric is longer than that of original cotton fabric. When the temperature exceeds 150 ℃ , it loses its temperature sensitivity, resulting in the crosslinked cotton fabric being insensitive to temperature. The most suitable polymer concentration is 1-8%. According to the DSC curve of P(MEO2MA-co-EGMA360) in the range of 60-20℃, the glass transition temperature (Tg) was determined. There is an obvious endothermic peak on the DSC curve near -26 ℃ , which indicates that the glass transition temperature of P(MEO2MA-co-EGMA360) is -26℃, and P (MEO2MA-EGMA360). It is in a viscous state at room temperature. The air permeability and moisture permeability of crosslinked cotton fabric can be adjusted by changing the temperature, and the wearing comfort of the fabric can be improved. The test results of fabric wearability show that after crosslinking reaction, the washing fastness and rubbing fastness of fabric are within acceptable range, while whiteness, softness and mechanical properties are not affected. Considering comprehensively, when the polymer concentration is 8%, the drying temperature is 130 ℃ and the drying time is 2min, the finished fabric has the best indexes. This is mainly due to the spontaneous "self-adjustment" of aggregation morphology between the hydrogen bonding between polymer and water molecules and the hydrophobic interaction between molecules themselves in order to maintain a delicate dynamic balance, thus reaching a new thermodynamic equilibrium state.